Keragaman Jenis Lalat Buah dan Tingkat Parasitisasi Parasitoid yang Berasosiasi dengan Tanaman Buah-Buahan di Distrik Lautem, Timor Leste - NOE OLIVIERA; I WAYAN SUSILA; I WAYAN SUPARTHA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
ABSTRACT Diversity of Fruit Flies and Parasitization Level of Parasitoid Associated with Plants Fruits in Lautem District, Timor Leste.           Research on diversity of fruit flies  and parasitization level of parasitoid   associated with Plants Fruit was done from November 19, 2014 up to Februari 2, 2015 in Lautem district, Timor Leste. The objectives of this research are to determine of diversity of fruit flies, percentage of damage, and parasitization level of parasitoid associated with fruits tree in Lautem District. The research using survey method and traps  made from plastic bottle filled chemical atraktan form Methyl eugenol, Cue-lure, and Dorsal lure installed in five sub District in Lautem District. The purpose of survey methods were to account percentage of damage fruit and parasitization level of parasitoids, while istaled traps aimed to know diversity of fruit plies, dominance, and similarity index.  The results of research indicated  that was pound 9 species of fruit flies there were Bactrocera dorsalis (Hendel), B. umbrosa (Fabricius), B. caudata (Fabricius), B. complicata  (White), B. cucurbitae (Coquillett), Dacus longicornis (Wiedemann), B. exornata (Hering) B. nigrotibialis (Perkins), B. albistrigata (de Meijere). Species diversity of fruit flies in Lautem district was low with diversity index < 1.5. The dominant species of fruit   was B. dorsalis (Hendel). Similarity index of fruit flies in each sub-district in Lautem were 50-88%.  Demage percentage of fruit fly on manggo (30%) higher than watermelon (24%), and rose apple (11%).  Parasitization level of parasitoids associated with fruit flies  in Lautem was low (28%). Species of parasitoids were found in Lautem district was Diachasmimorpha longicaudata (Insect: Hymenoptera: Braconidae). Keywords:  Fruits, Fruit Flies, and parasitoids.